2009
DOI: 10.1016/j.atherosclerosis.2008.11.009
|View full text |Cite
|
Sign up to set email alerts
|

PPARgamma Promoter Polymorphisms and Acute Coronary Syndrome

Abstract: The protective role of 93695C>T polymorphism in PPARg promoter in ACS suggests that PPARg genetic variants may affect the susceptibility to atherosclerotic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…8 of the 22 qualified studies were prospective [22], [36], [43], [44], [53], [54] and the others were retrospective. 11 studies were population-based (P–B) [22], [36], [44], [47], [49], [50], [52]–[54] and the rest half were hospital-based (H–B). 15 studies were analyzed for CAD [22], [36], [42], [43], [47], [48], [50], [51], [54] as the primary outcome, 2 studies for ACS [49], [53] and 5 studies for MI [18], [21], [23], [44], [52] as an end point.…”
Section: Resultsmentioning
confidence: 99%
“…8 of the 22 qualified studies were prospective [22], [36], [43], [44], [53], [54] and the others were retrospective. 11 studies were population-based (P–B) [22], [36], [44], [47], [49], [50], [52]–[54] and the rest half were hospital-based (H–B). 15 studies were analyzed for CAD [22], [36], [42], [43], [47], [48], [50], [51], [54] as the primary outcome, 2 studies for ACS [49], [53] and 5 studies for MI [18], [21], [23], [44], [52] as an end point.…”
Section: Resultsmentioning
confidence: 99%
“…We next created a Galbraith plot to graphically assess the source of the heterogeneity. As a result, five studies 15,28,32,34,37) were identified as the main contributors of heterogeneity for the allelic models, two studies 15,37) were identified as the main contributors of heterogeneity for the additive and recessive models and four studies 11,28,32,37) were identified as contributors of heterogeneity for the dominant model (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of this SNP was weakening with the presence of P12P homozygote genotype [46]. Moreover, in an Italian cohort, the 93695C > T PPARγ promoter polymorphism was found to have a protective role in acute coronary syndrome [56]. Furthermore, the C1431T PPARγ polymorphism was associated not only with altered plasma lipids during fasting but also with higher risk of an angiography defined CVD [47].…”
Section: Human Aspects Of Pparγ In Metabolic Syndromementioning
confidence: 99%